Effect of different extraction methods on yield and physico-chemical properties of garden cress (Lepidium sativam L.) oil (Journal of Oilseed Brassica, 2026)
Effect of different extraction methods on yield and physico-chemical properties of garden cress oil was studied. Oil from the dried garden cress seeds were extracted by screw press, solvent extraction (without heating) and soxhlet extraction method. Physical properties studied were specific gravity, viscosity and colour, whereas, chemical properties analyzed were peroxide value, acid value and iodine value. Soxhlet extraction was found to give highest yield of oil. Non-significant difference was observed for specific gravity of oil extracted by all methods. Viscosity of the oil extracted with screw press was highest (53.7 mPa.s) than solvent extracted oil and soxhlet extracted oil (39.9 and 42.7 mPa.s, respectively). Oil extracted by soxhlet method was darker in colour than the solvent extracted. Peroxide value (2.53 meq.kg-1) and acid value (0.74 mg KOH.g-1) were higher for oil extracted with the soxhlet extraction method followed by solvent and screw press extraction method (1.27, 0.69 meq.kg-1 and 0.83, 0.61 mg KOH.g-1, respectively) whereas, iodine value was highest (134.2 g I2.100g-1) for solvent extraction method followed by soxhlet extraction and screw press method (131.7, 97.3 g I2.100g-1, respectively). Fatty acid profile and tocopherols content analysis of the oil extracted by soxhlet method showed that, garden cress seed oil contains 34.46 % of alfa linolenic acid and 971.6 ppm total tocopherols. Oil stored in polyvinyl terephthalate bottle for 90 days showed significant increase in peroxide (25.8meq.kg-1).